Establecemos y Ordenamos. un análisis Comparado de Los Estatutos y Constituciones de Los Siete Colegios Mayores Españoles (siglos XIV-XVII). con una Transcripción de Las Constituciones y Estatutos Del Colegio de Santa Cruz de Valladolid. - Lario, Dámaso de (Dykinson, S.L., 2021)
The purpose of this book is to make a comparison the books of statutes of the seven Spanish elite colleges - the colegios mayores - and their changes throughout the time. To do so those books have been deconstructed first and reordered later, in accordance with the type of members of the college communities, their internal organization, core values and rules regarding daily life and the protection and control of the colleges. In practical terms this work is a companion book of part II of Escuelas de imperio. La formación de una elite en los Colegios Mayores (siglos XVI-XVII) (2019), where the foundations of the Spanish collegiate system are analyzed. The book includes a transcript of the constitutions and statutes of the College of Santa Cruz in Valladolid, whose last printed edition is from 1786.
Description based upon print version of record.
Keywords: Colegio Mayor de Santa Cruz (Valladolid, Spain) -- Constitution.; Colegio Mayor de Santa Cruz (Valladolid, Spain); Education, Higher -- Spain -- History -- Sources.; Universities and colleges -- Spain -- History -- Sources.; Enseignement supérieur -- Espagne -- Histoire -- Sources.; Education, Higher; Universities and colleges; Spain; Education; Educación; Historia; History; Universidades; Universities; Colegios Mayores; Secular colleges; Estatutos y Constituciones; College statutes; Burocracia moderna; Early modern bureaucracy; Constitution; Sources